Faux anévrysme de l’artère radiale post-traumatique : à propos d’un cas et revue de la littérature - GANIOU TIDJANI Kabirou; MOUSSA ABDOU Taofik; KANE KAKA Mahaman Mouhtari; OUMAROU HAMIDO Kadri; GUIDAH Saidou, (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2025)
Introduction: Hand trauma is quite common. In France, there are more than 1,400,000 per year, including a significant proportion of wounds. Post-traumatic localized false aneurysm of the radial artery is a rare entity. The authors report a case of a post traumatic false aneurysm of the radial artery, partially thrombosed. Observation : This paper presents the case of a 24-year-old female patient with no significant medical history, who experienced trauma to the right upper limb two years before from a motorcycle accident. Upon clinical examination, swelling was noted in the anterior part of the forearm. Palpation detected a pulse. Standard radiography revealed no fractures or dislocations. Ultrasound imaging of the forearm identified a heterogeneous hypoechoic mass within the anterior soft tissues, aligned with the radial artery. Doppler study indicated partial vascularization of the mass, exhibiting a "back and forth" Doppler pattern. Conclusion : Upper limb trauma is common, but aneurysmal complications are rare. This case report describes a partially thrombosed false aneurysm of the radial artery at its distal part. The patient did not receive treatment due to being lost to follow-up.